Analysis of silica sand distribution and Grain Fineness Number (GFN) for Casting Process - Komarudin, Udin; Farida, Ida; Santoso, Heru (International Journal of Psychosocial Rehabilitation, 2020)
Silica sand is one type of sand that is sought after by industries, especially industries engaged in metal casting, because this sand can be used as a molding material. Besides being easily formed, silica sand can achieve maximum hardness after being mixed with chemicals, namely resins and catalysts. To achieve the maximum strength of the sand mold, curing time is required. This curing time provides the time / opportunity for the resin and catalyst to react so that the mold reaches its maximum strength. This study aims to determine the distribution of sand and the value of GFN (Grain Fineness Number) to determine the suitability of sand with the physical requirements of sand for casting iron. Testing of sand distribution is carried out on new, reclaimed, and mixed silica sand using the Sieve Analysis Test Type PSA (GP) (Laboratory Siever). The test was carried out within 15 minutes with vibration 8. Analysis results showed that the most recent sand distribution was in the 0.5 mm sieve, namely 29.61 g or 59.22%, with GFN = 27.8. The most reclamation sand distribution is in the 0.355 mm sieve, which is 15.65 gr or 31.3% with GFN = 43.53. And the most mixed sand distribution was at 0.355 mm sieve, which was 15.68 gr or 31.36% with GFN = 39.6. Sand that meets the physical requirements for the cast iron casting process is reclaimed silica sand.